THE INCREASE IN INVESTMENT ATTRACTIVENESS OF COMMERCIAL ENTERPRISES - O. Volik; O. Solntseva; J. Tsunaeva (Вестник университета)
The increase in investment attractiveness contributes to the successful development and growth of a commercial enterprise, allowing to function in modern conditions of high competition. The issue of attracting investment for the effective functioning of an enterprise as well as necessary conditions and factors of investment attraction. is discussed in the article. Particular attention is paid to assessment which allows to identifiy the most attractive enterprises for investment. The positive experience of investment attraction on the example of commercial project of management in trade and warehouse accounting is analysed. The review of international and domestic experience concludes that to attract investment a company should adhere to a certain algorithm.